Investigating economywide and household-level impacts of sector-specific shocks in a poor country: The case of avian flu in Ethiopia - Ayele, Gezahegn; Birol, Ekin; Diao, Xinshen; Asare-Marfo, Dorene; Roy, Devesh; Thomas, Marcelle (International Food Policy Research Institute, 2010)
Do the economic effects of potential avian flu outbreaks justify policy attention and resource allocation in a poor country like Ethiopia? We address this question by assessing both economywide (macro-level) economic impacts and household (micro-level) livelihood impacts that might be caused by an avian flu outbreak in Ethiopia. Because 1) the prevalent traditional poultry sector is weakly linked to other sectors, 2) livelihoods of the poultry-producing households are diversified, and 3) shocks are idiosyncratic in nature, the study finds that the impacts of an avian flu outbreak are likely to be small and limited to producers who keep larger flocks. Therefore, allotment of funds to prevent the disease must be justified on the grounds of preventing spread of the disease to human populations in Ethiopia and in other countries where it might have more severe economic and health effects. In other words, resource allocation must be justified as a global public good.